2021
DOI: 10.1111/pbr.12908
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci and candidate genes responsible for pale green flesh colour in watermelon (Citrullus lanatus)

Abstract: Watermelon (Citrullus lanatus) is a fleshy, sweet fruit that has become one of the most popular horticultural crops worldwide. Fruit flesh colour is an important commercial trait that guides consumer choice and watermelon breeder selection. Flesh colour is determined by different compositions of chlorophyll and carotenoids (Zhang et al., 2016). Variations in watermelon flesh colour have been designated as scarlet red, red, pink, orange, canary yellow, pale yellow, and white based on carotenoid composition. Red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In the last decade, whole genome SNP-derived CAPS markers have emerged as potential genetic markers for uncovering the genetic regions affecting complex types of qualitative and quantitative traits in differentially derived populations of unexplored botanical groups. For example, powdery mildew resistance (Li et al, 2017 ), stripped fruit skin (Liu et al, 2019 ), ovary-fruit associated morphology (Amanullah et al, 2018 , 2020 , 2021 ), plant height (Zhang et al, 2021 ), pale green and dark red color flesh (Wang et al, 2019 ; Pei et al, 2021 ), egusi seed traits (Osae et al, 2021 ), and fruit peel hardness (Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, whole genome SNP-derived CAPS markers have emerged as potential genetic markers for uncovering the genetic regions affecting complex types of qualitative and quantitative traits in differentially derived populations of unexplored botanical groups. For example, powdery mildew resistance (Li et al, 2017 ), stripped fruit skin (Liu et al, 2019 ), ovary-fruit associated morphology (Amanullah et al, 2018 , 2020 , 2021 ), plant height (Zhang et al, 2021 ), pale green and dark red color flesh (Wang et al, 2019 ; Pei et al, 2021 ), egusi seed traits (Osae et al, 2021 ), and fruit peel hardness (Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MELO3C011657 encodes the tetrapyrrole-binding protein, which has been significantly demonstrated in the Arabidopsis papp5 mutant, and it has been shown that the tetrapyrrole-binding protein is mainly associated with PAPP5 in complex components involved in the downstream of the plastid signaling pathway of tetrapyrrole Mg-ProtoIX/Mg-ProtoIX-ME [ 58 ]. The complexity of these components can act as a negative regulator of PhANG expression during chloroplast development, which ultimately affects the chloroplast morphology associated with plant flower color morphology [ 59 ]. Most importantly, we believe that our current research findings demonstrate comprehensive bio-information about the candidate pathways and associated genes involved in the determination of melon stigma color.…”
Section: Discussionmentioning
confidence: 99%
“…A SNP marker linked to the lycopene b-cyclase gene ( LCYB ) has been developed for genotype selection ( Bang et al, 2007 ). Kompetitive allele-specific polymorphism markers co-segregating with pale flesh color phenotype have been developed for genetic analysis of watermelon ( Pei et al, 2021 ). The KASP marker ( chr06_7040350 ) effectively distinguished white and pale-yellow fleshed watermelons useful for marker-assisted breeding ( Wang et al, 2017 ).…”
Section: Molecular Markers and Quantitative Trait Loci Analysis Of Ph...mentioning
confidence: 99%
“…Also, the β-carotene hydroxylase CHYB gene (gene ID: Cla011420 ) was mapped on chromosome 1 ( Jin et al, 2019 ). The QTL qfc10.1 located on chromosome 10 provides the pale flesh color of watermelon ( Pei et al, 2021 ). Carotenoid biosynthesis enzymes carotenoid isomerase gene ( CRTISO ; gene ID: Cla017593 ) is located on chromosome 10 ( Jin et al, 2019 ).…”
Section: Molecular Markers and Quantitative Trait Loci Analysis Of Ph...mentioning
confidence: 99%